ANALISIS BREAK EVENT POINT TERHADAP PERENCANAAN LABA PADA PERUSAHAAN GARAM PT. HEROES ADHI MULIA PONTIANAK - Didi Rahmat; Muhammad Yusuf (STIE 'INDONESIA' Pontianak, 2014)
This Research takes the focus at how to conduct the planning of company profit at calculation of Break Event Point. Becoming variable is Break event point and company profit. Method used in replying problems are quantitative descriptive, with the analysis of trend and method regression in profit forecasting. Result of above data analysis that level of Break Event Point planning can give the motivation which do well by the planning of profit growth. more higher GAP that happened among break event point with the profit planning started from year 2011 as basic data up to 2013, showing that level of advantage acquirement for the year of 2014 up to 2018 with the level of lower break event point. So that totalize the sale which must be fulfilled can be at the profit condition progressively lowers. in other side dissimilar profit planned more higher.